Pengaruh Pemberian Kolkisin Terhadap Morfologi Cabai Merah (Capsicum Annuum L.) - Putra, Aditya Willy; Sahara, Fitri; Ritonga, Ilham Rizky; Ramadhani, Sari; Wardhani, Tasya Evi; Achyar , Afifatul (Prosiding Seminar Nasional Biologi, 2021)
Red chili peppers (Capsicum annuum L.) as one of the vegetable commodities of high economic value and have a fairly bright prospect in an effort to improve the standard of living of farmers. In vitro propagation of plants with mutation induction is an alternative method to increase the genetic diversity of plants. Induction of mutations can be done by giving Colchicine to the plant. The use of Colchicine to create crops through chemical mutation methods has been widely done in the agricultural world, tetraploid and diploid crops have different morphological structures. This study aims to determine the effect of Colchicine on the morphology of red chili peppers (Capsicum annuum L.). There are 2 treatments namely control and Colchicine 0.01 ml, of which there are 5 samples each. The observed parameters are the number of leaves, the length of the stem and the width of the leaves. The results of this study showed that the sample given Colchicine has a smaller number of leaves, stem length and leaf width than control. This happens because the cells given Colchicine do not experience cell division so that the growth of red chili peppers becomes slower.